2016
DOI: 10.1108/prt-08-2015-0082
|View full text |Cite
|
Sign up to set email alerts
|

Photocatalytic activity of ZnO-MnO2 core shell nanocomposite in degradation of RhB dye

Abstract: Purpose The purpose of this study is to synthesize a semiconductor photocatalyst which responds to both UV light and visible light in removal of organic dyes. Design/methodology/approach ZnO nanoparticles were pre-synthesised via sol-gel method using zinc nitrate tetrahydrate and methanamine at 90°C for 20 h. Subsequently, the as-synthesised ZnO nanoparticles were filtered, washed and dried. To synthesize ZnO-MnO2 core shell nanocomposites (CSNs), 2:3 M ratio of KMnO4 and MnSO4 solution was stirred for an ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…The peak at 502 cm −1 in S 1 , S 2 , and S 3 is attributed to the characteristic absorption peak of the Zn-O bond and also confirms the presence of ZnO in all samples [20]. The peaks at 622 cm −1 and around 1010-1122 cm −1 in S 2 and S 3 illustrate the stretching of O-Mn-O lattice vibrations [1,38]. The wideband at 3000-3600 cm −1 assigned to the -OH band [39,40].…”
Section: Resultssupporting
confidence: 56%
“…The peak at 502 cm −1 in S 1 , S 2 , and S 3 is attributed to the characteristic absorption peak of the Zn-O bond and also confirms the presence of ZnO in all samples [20]. The peaks at 622 cm −1 and around 1010-1122 cm −1 in S 2 and S 3 illustrate the stretching of O-Mn-O lattice vibrations [1,38]. The wideband at 3000-3600 cm −1 assigned to the -OH band [39,40].…”
Section: Resultssupporting
confidence: 56%
“…Both the XRD and microscopic characterizations indicate that, in the case of the Zn x Mn 3−x O 4 oxides, real mixed oxides were formed with only one type of morphology. This was not the case for the studies carried out by Pung et al ( 2016 ), in which a ZnO–MnO 2 core–shell nanocomposite was formed, or by Wang et al ( 2019 ), in which both oxides were mixed to form a composite material that maintained both structures. In the study reported by Li et al ( 2008a ), the effects of the presence of MnO 2 on the photocatalytic degradation of phenol by TiO 2 and ZnO were investigated.…”
Section: Resultsmentioning
confidence: 94%
“…Thus, the design and development of low-cost, high-performance catalysts that are preferably sustainable and active across the entire solar spectrum should be key objectives. Several researchers have evaluated the photocatalytic activities of MnO 2 -TiO 2 (Li et al, 2008a ) and MnO 2 -ZnO (Pung et al, 2016 ) mixtures. However, lower photocatalytic activity was observed for ZnO and TiO 2 in the presence of MnO.…”
Section: Introductionmentioning
confidence: 99%
“…In order to improve the adsorption and dye degradation efficiency by using graphene-based nanomaterials, along with co-catalysts, noble metal particles, metallic, non-metallic doping and with hydrogels have been used [ 18 ]. Even though many researchers reported on the dye degradation of RhB, our work using graphene based nickel nanocomposite (RGO–Ni) showed better adsorption efficiency than adsorption for removing RhB dye compared to that of other adsorbents like TiO 2 and graphene TiO 2 [ 19 ], CuS/PVA nanocomposite [ 20 ], ZnO–MnO 2 [ 21 ], and other self-assembled GO nanostructures from various styles [ 22 , 23 , 24 , 25 ].…”
Section: Introductionmentioning
confidence: 98%